Figurative Language Used in King Lier Novel by Willian Shakespeare: Explorer Literary Appreciation - Saputra, Frian; Kurniawati, Ari; Yuniarti, Vyna; Hayati, Sri (Journal of English Education, 2024)
This study explores the use of figurative language in William Shakespeare's "King Lear," examining how literary devices such as metaphors, similes, personification, hyperbole, and irony contribute to the play's thematic and emotional depth. Through a comprehensive analysis, the research highlights how Shakespeare's linguistic choices enhance the narrative complexity and deepen the audience's engagement with the characters and themes. Metaphors succinctly convey complex ideas and emotions, similes vividly depict characters' experiences, personification imbues abstract concepts with human characteristics, hyperbole emphasizes emotional intensity, and irony underscores the contradictions and tragic outcomes within the play. The findings have practical implications for literary education, providing a framework for educators to enhance students' analytical skills and appreciation of Shakespearean drama.